Student dropout in primary and secondary education in the Republic of Serbia - Krstić Ksenija (Psihološka Istraživanja, 2017)
Student dropout from school is a serious problem in educational systems all over the world. This paper will provide an overview of the various dropout definitions and their consequences for measuring and monitoring. Since a diversity of factors (individual, familial, school and systematic) is connected with student attrition in foreign research, the attempt has been made to systematise their results and provide data regarding similar Serbian studies. Considering the fact that there are no systematic analyses of students’ dropout rate in Serbia, the existing data from primary and secondary schools from a variety of statistical sources will be presented. We conclude that one way to reduce dropout in Serbia is to further develop research interest in the topic, as well as the strategies for monitoring, prevention and intervention.